Faktor-Faktor yang Berhubungan dengan Risiko Depresi Postpartum - Oktavia Ramadhani Saputri; Niken Sukesi (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Postpartum depression is a mood disorder that occurs in mothers after childbirth, with symptoms that can appear from pregnancy until 4 weeks postpartum. This condition negatively impacts the psychological health of the mother and the development of the baby. This study aims to analyze factors associated with the risk of postpartum depression. The method used was quantitative with an analytical survey design through a cross-sectional approach. Data collection was carried out using the Edinburgh Postnatal Depression Scale (EPDS) questionnaire consisting of 10 questions. The results of the validity test showed a calculated r value of > 0.3610 and the reliability test obtained a Cronbach's alpha value of 0.67. The study sample consisted of 42 respondents selected using a total sampling technique, with inclusion criteria of mothers aged ≥18 years, in the period <6 weeks postpartum, and willing to be respondents. Data analysis used the chi-square test. The results showed that all variables had a significant relationship with the risk of postpartum depression (p < 0.05). These variables include age (p=0.040), education (p=0.018), occupation (p=0.011), history of depression (p=0.024), complications (p=0.017), economic status (p=0.048), parity (p=0.016), type of delivery (p=0.006), husband's support (p=0.000), and family support (p=0.028). Therefore, it can be concluded that demographic, obstetric, and social support factors play an important role in the risk of postpartum depression. These results are expected to form the basis for prevention efforts and early intervention to improve postpartum maternal mental health.